The Role of the Indigenous Guaraní Kaiowá Woman in Land Recognition - Pacheco, Isabela Stefanes (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2013)
This article deals with the presence of indigenous women in processes of recognition for traditional lands. Over the course of the twentieth century, indigenous Brazilians have been at the center of manifestations in defense of their lands. In 1980 they started a powerful social and political reconstruction process in order to obtain recognition as an ethnically differentiated people. Although it implies significant progress, the inclusion of women in politics is a complex process, since it depends on factors such as the dichotomy between tradition and modernity, and indigenous politics. This article studies the process of Guaraní Kaiowá women in Mato Grosso del Sur, Brazil.